Conducting action research for business and management students - Coghlan, David; Shani, Abraham B. (Los Angeles ; London ; New Delhi : SAGE Publications, 2018)
"Action research is an interactive approach to studying real social and organizational issues and those who experience them with the goal of solving particular problems or improving practice while also creating knowledge or theory as the action unfolds. This book explains how action research differs from more detached research methods and gives you expert guidance on how to engage in action research effectively. A well-managed action research project can lead to the preparation of a good dissertation, as well as produce knowledge that is relevant and adds value for the organization involved in the project." Back cover
1. Introducing Action Research -- 2. Understanding Action Research -- 3. Components of Action Research -- 4. Enacting Action Research -- 5. Examples of Action Research -- 6. Conclusions.
Includes bibliographical references (pages 117-124) and index.
Keywords: Action research; Business -- Research -- Methodology; Management -- Research -- Methodology; Action research; Business -- Research -- Methodology; Management -- Research -- Methodology; Business and Management